Religious Ambivalences as a Source of Change in Early Buddhisms - Iori, Elisa (2025)
This article addresses the formation of Buddhisms against the backdrop of the double ambivalence its practitioners had between (a) the religion of the Buddha and local religious practice, and (b) between the physical and conceptual spaces of the wilderness and the urban. Such tensions internal to the religious field are considered paramount to unpacking and analyzing the transformations of Buddhism, as they hold the potential for religious changes. The first section presents some examples of temporary and situational subversion of power relations between divine entities, Buddha, and metapersons, as well as spatial consequences of unsolved tensions. By focusing on the northern Gandharan context, the second section discusses two cases in which the Gandharan urban culture acts as a booster and stabilizer of ambivalence-driven changes in the religious field in regard to the Buddhist doctrine and authorized media of communication.